Multidisciplinary treatment of fracture-related infection has a positive impact on clinical outcome: a retrospective case control study at a tertiary referral center - Rupp, Markus; Walter, Nike; Popp, Daniel; Hitzenbichler, Florian; Heyd, Robert; Geis, Sebastian; Kandulski, Melanie; Thurn, Sylvia; Betz, Thomas; Brochhausen, Christoph; Alt, Volker (Antibiotics, 2023)
Objectives: Fracture-related infection (FRI) is a major complication in orthopedic and trauma surgery. The management and choice of treatment can be difficult depending on multiple factors. Therefore, we implemented a weekly multidisciplinary team discussion to determine diagnostic and treatment strategies in FRI patients and aimed to analyze its effect on clinical outcomes. Methods: Clinical outcomes of FRI patients treated before and after implementation of a structured multidisciplinary treatment (MDT) approach with a weekly case discussion were compared at a follow-up of 12 months. Results: In total, n = 117 were eligible for enrolment, whereby n = 58 patients (72.4% male, mean age 56.7 ± 16.8 years) constituted the MDT group and n = 59 patients (72.9% male, mean age 55.0 ± 16.5 years) the control group. In the MDT group more cases were treated with local antibiotics (67.2% vs. 27.1%, p < 0.001) and significant less amputations (3.4% vs. 6.8%, p = 0.014), as well as less revision surgeries (1.5 ± 1.2 (0-5) vs. 2.2 ± 1.2 (0-7), p = 0.048) were performed. A trend towards less debridement, antibiotics and implant retention (DAIR) procedures, lower rates of recurrence of infection and less treatment failures in the MDT group was observable, even though not statistically significant. Conclusion: An MDT approach providing a patient tailored treatment concept in the treatment of FRI patients appears to be beneficial for the affected patients. Quality and efficacy of implemented MDT meetings should further be evaluated to provide sufficient evidence to further implement this valuable tool in clinical practice and decision making.